Tamoxifen Rechallenge Decreases Metastatic Potential but Increases Cell Viability and Clonogenicity in a Tamoxifen-Mediated Cytotoxicity-Resistant Subline of Human Breast MCF7 Cancer Cells - Chang, Yung-Chieh; Cheung, Chun Hei Antonio; Kuo, Yao-Lung (Frontiers in Cell and Developmental Biology, 2020)
Background: Drug resistance is frequently found in estrogen receptor-positive (ER+) breast cancer patients during and after prolonged tamoxifen treatment. Although tamoxifen challenge has been proposed for treating recurrent breast tumors, the clinical benefit of this treatment is still controversial. The aims of this study are to identify the possible tamoxifen cytotoxicity-resistant subpopulation of MCF7 cells and to determine the effects of tamoxifen rechallenge on these cells. Methods: Western blot analysis was used to determine the expression levels of various epithelial–mesenchymal transition (EMT)- and cell survival/proliferation-related proteins in MCF7 and MCF7-derived, tamoxifen-resistant MCF7-TAM12.5 breast cancer cells. Wound healing, Transwell migration and invasion assays were used to examine the metastatic potential of cells. Clonogenic assays, trypan blue exclusion assays and bromodeoxyuridine (BrdU) assays were used to examine clonogenicity and to determine the proliferation rate of cells. Results: We found that MCF7-TAM12.5 cells exhibited higher tolerance to tamoxifen-mediated cytotoxicity, higher metastatic potential, higher expression levels of XIAP, and lower expression levels of ERα/ERβ/HER2/Smac than MCF7 cells. In addition, MCF7 cells endogenously expressed Bcl-2α, whereas MCF7-TAM12.5 cells only expressed Bcl-2β. Interestingly, tamoxifen rechallenge decreased the metastatic potential but increased the proliferation and clonogenicity of MCF7-TAM12.5 cells. At the molecular level, tamoxifen rechallenge upregulated the expression of phosphorylated aurora-A and aurora-B kinase in MCF7-TAM12.5 cells. Conclusions: Our findings further support the existence of highly heterogenetic cancer cell populations in ER+ breast tumors. It will be of clinical importance to determine the protein expression and the genetic profiles of tamoxifen-resistant/recurrent ER+ breast tumors to predict the potential effects of tamoxifen readministration in the future.